Strategi Implementasi TIK Untuk Meningkatkan Efektivitas Manajemen dan Pembelajaran di Sekolah Menengah Pertama - Anasari, Tri; Abdillah, Definka Puan Shalika; Sulistiyowati, Nourma Ayu; Soekarno, Gustina Anugerahwati; Murtiyasa, Budi; Masduki, Masduki (TIN: Terapan Informatika Nusantara, 2025)
This study aims to analyze the strategy of implementing Information and Communication Technology (ICT) in improving the effectiveness of school management and the quality of learning. The study uses a qualitative approach with a case study method, focusing on schools that have implemented ICT in managerial activities and teaching and learning processes. Data were collected through interviews, observations, and document analysis, involving various parties such as principals, administrative staff, teachers, and students. The analysis was conducted using a triangulation approach of sources and methods, and supported by a SWOT analysis to identify strengths, weaknesses, opportunities, and challenges in the implementation of ICT. The research strategically strengthened the school management system through administrative efficiency, increased data accuracy, and more integrated monitoring of academic performance. The results of ICT implementation also contributed to increased teacher interaction as shown by a total average of 4.03 that teachers have a positive perception of ICT implementation, especially in the aspects of leadership support (average 4.60) and availability of facilities (4.50). Student results show a total average of 3.91 students rating the implementation of ICT in schools as Good, with the most prominent aspects being more engaging learning (4.25) and the convenience of learning using ICT (4.10). However, several obstacles remain, such as limited digital infrastructure, a lack of teacher competence in mastering technology, and resistance to changes in work culture. As recommendations, this study offers three main steps in ICT implementation: (1) gradually strengthening digital infrastructure according to school needs, (2) improving educator competence through training based on real needs, and (3) implementing a flexible and sustainable ICT management evaluation system. With the support of visionary school policies and increased digital literacy among all school members, digital transformation is expected to create an innovative, collaborative, and quality-oriented learning ecosystem in the digital era.